The Marginal Character’s Specificity in the Texts of German Writers Representing the 1968 Generation - Maryna Orlova (Pitannâ Lìteraturoznavstva)
This article is an attempt of the interdisciplinary research of different sciences studying the phenomena of marginality, namely sociology, history, culturology and the study of literature. As the base of this research, the investigations from the theory on sociological marginality were taken (N. Akopyan, O. V. Butylina, J. S. Vorobyova, O. N. Makarenko, J. Mancini.)